The influence of whole body vibration on knee extensor stiffness and functional performance - Owen, G. J. (2004)
The use of vibration as an exercise intervention offers new possibilities for coaches, clinicians, and strength and conditioning practitioners. It appears that muscle activation by means of vibration may induce improvements in strength and power similar to those observed with conventional strength training. Furthermore, vibration is thought to affect the neuromuscular functions that regulate muscle stiffness. There has been preponderance in the literature to assume that the stiffness properties of the muscle affect muscle function, which in turn affects functional performance. Improving functional performance is a major goal for recreational to elite athletes. However, improving the performance of well-trained athletes, especially whilst engaged in in-season training, is challenging, as the training status of such athletes is near optimal. Furthermore, training and playing schedules usually do not allow for adequate training frequencies. Therefore, the application of in-season vibration training may offer a means by which substantial loading can be placed upon the athlete with minimal interference to the weekly schedule. Consequently, the aims of this thesis were to: 1) determine the reliability of a new method to measure the stiffness of the knee extensor muscles; 2) investigate the relationship between knee extensor stiffness, strength, power, and speed; and 3) examine the effect six weeks of squat training with and without whole body vibration (WBV) has on knee extensor stiffness, strength, power, and speed.